Failure of a Popular Legislative Candidate: a Case Study in Rias Village - M. Akmal; Khairul Amin; Halik Halik (FISIP Universitas Malikussaleh, 2022)
This study aims to describe the failure of the legislative candidate in the 2019 election in Rias village, Toboali District, Southern Bangka Regency, Bangka Belitung Islands Province. This study is based on the fact that Rias village is one of the villages that has a very large number of fixed voters, even the largest in the Southern Bangka district. However, despite a large number of voters, there is still not a single member of the community of Rias Village who has succeeded in becoming a legislative councilor. This study focuses on two key points: how communities perceive candidates' failures and what factors contribute to their failure. The method used in this study is a qualitative one with a descriptive approach, with data obtained from in-depth interviews. The study shows that there are five factors that cause the failure of popular legislative candidates in Rias Village, i.e., political constellation, public political behavior, political actors, successful teams, and political costs. The community also had a notion that the same thing happened as a factor in the failure of a legislative candidate in Rias Village.